Recent advances in tendon tissue engineering strategy - Ning, Chao; Li, Pinxue; Gao, Cangjian; Fu, Liwei; Liao, Zhiyao; Tian, Guangzhao; Yin, Han; Li, Muzhe; Sui, Xiang; Yuan, Zhiguo; Liu, Shuyun; Guo, Quanyi (Frontiers in Bioengineering and Biotechnology, 2023)
Tendon injuries often result in significant pain and disability and impose severe clinical and financial burdens on our society. Despite considerable achievements in the field of regenerative medicine in the past several decades, effective treatments remain a challenge due to the limited natural healing capacity of tendons caused by poor cell density and vascularization. The development of tissue engineering has provided more promising results in regenerating tendon-like tissues with compositional, structural and functional characteristics comparable to those of native tendon tissues. Tissue engineering is the discipline of regenerative medicine that aims to restore the physiological functions of tissues by using a combination of cells and materials, as well as suitable biochemical and physicochemical factors. In this review, following a discussion of tendon structure, injury and healing, we aim to elucidate the current strategies (biomaterials, scaffold fabrication techniques, cells, biological adjuncts, mechanical loading and bioreactors, and the role of macrophage polarization in tendon regeneration), challenges and future directions in the field of tendon tissue engineering.